Interactions between healthcare personnel and family caregivers of people with dementia from minority ethnic backgrounds in home‐based care—An explorative qualitative study. (21st November 2021) - Gulestø, Ragnhild; Lillekroken, Daniela; Bjørge, Heidi; Halvorsrud, Liv
Abstract: Aims: To explore how healthcare personnel in home‐based care perceive interactions with family caregivers of people with dementia from minority ethnic backgrounds. Background: Research shows that the organization of home‐based care rarely allows opportunities to provide support to family caregivers in practice. However, how these organizational structures influence the way in which healthcare personnel perceive their interactions with family caregivers of people with dementia from minority ethnic backgrounds remains an unexplored area. Design: An explorative qualitative study inspired by a critical realist approach using Pierre Bourdieu's theoretical concepts of field, habitus and capital. Methods: Data were collected through individual semi‐structured interviews with six nurses and four auxiliary nurses employed in home‐based care in Norway. The data were analysed using a thematic analysis approach. The participants were recruited in September and October 2020. Findings: 'Family caregivers perceived as facilitators of or barriers to collaborative care' was identified as an overarching theme, supported by two main themes: 'Preconditions for successful collaboration' and 'Challenges for collaborative relationships'. The findings revealed that the participants mainly focused their attention on the dementia patients from minority ethnic backgrounds, while they felt that the family caregivers influenced the way in which they provided healthcare. Conclusions: The findings demonstrate that timesaving strategies have a major influence on healthcare personnel's perceptions of family caregivers from minority ethnic backgrounds. Attention towards the needs of the family caregivers was often replaced by evaluations of their usefulness in the provision of healthcare to the dementia patients. Impact: This study raises concerns about home‐based care as a rigid and inflexible system. It therefore provides opportunities to raise questions on status quo, stimulate debate and encourage fresh thinking with regards to the support and inclusion of family caregivers in the home‐based care system for people with dementia from minority ethnic backgrounds.